Stress responses in Crassostrea gasar exposed to combined effects of acute pH changes and phenanthrene - Lima, Daína (2020)
Ocean acidification is a result of the decrease in the pH of marine water, caused mainly by the increase in CO2 released in the atmosphere and its consequent dissolution in seawater. These changes can be dramatic for marine organisms especially for oysters Crassostrea gasar if other stressors such as xenobiotics are present. The effect of pH changes (6.5, 7.0 and 8.2) was assessed on the transcript levels of biotransformation [cytochromes P450 (CYP2AU1, CYP2-like2) and glutathione S-transferase (GSTΩ-like)] and antioxidant [superoxide dismutase (SOD-like), catalase (CAT-like) and glutathione peroxidase (GPx-like)] genes, as well as enzyme activities [superoxide dismutase, (SOD), catalase (CAT), glutathione reductase (GR), glutathione-S-transferases transferase (GST) and glucose-6-phosphate dehydrogenase (G6PDH)] and lipid peroxidation (MDA) in the gills of Crassostrea gasar exposed to 100 μg·L-1 of phenanthrene (PHE) for 24 and 96 h. Likewise, the PHE burdens was evaluated in whole soft tissues of exposed oysters. The accumulation of PHE in oysters was independent of pH. However, acidification promoted a significant decrease in the transcript levels of some protective genes (24 h exposure: CYP2AU1 and GSTΩ-like; 96 h exposure: CAT-like and GPx-like), which was not observed in the presence of PHE. Activities of GST, CAT and SOD enzymes increased in the oysters exposed to PHE at the control pH (8.2), but at a lower pH values, this activation was suppressed, and no changes were observed in the G6PDH activity and MDA levels. Biotransformation genes showed better responses after 24 h, and antioxidant-coding genes after 96 h, along with the activities of antioxidant enzymes (SOD, CAT), probably because biotransformation of PHE increases the generation of reactive oxygen species. The lack of change in MDA levels suggests that antioxidant modulation efficiently prevented oxidative stress. The effect of pH on the responses to PHE exposure should be taken into account before using these and any other genes as potential molecular biomarkers for PHE exposure.